Does Venture Capital Syndication Spur Employment Growth and Shareholder Value? Evidence from German IPO Data - Erik E. Lehmann (Max Planck Institute for Research into Economic Systems, 2004)
This study examines empirically the syndication of equity by multiple venture capitalists in Germany. Following the literature, there are mainly two competing views as to why venture capitalists syndicate investments. First, syndication can be viewed as a means of risk-sharing. Second, venture capitalists may provide important productive resources to firms, capital and information. We test hypotheses based on these two aspects. The results show that the syndication of equity and the number of venture capitalists involved cannot be fully explained by firm characteristics like size, age or industry affiliation. Although syndicated investments do not differ significantly in stock-market performance, they show significantly higher growth rates.
Keywords: G24; G32; 330; Zusammenschluss von Kapitalgebern; Venture Capital; Human Capital; Syndication; Firm Performance; Risikokapital; Kartell; Unternehmensgründung; Finanzierung; Börsenkurs; Unternehmenswachstum; Beschäftigungseffekt; Deutschland